Jornalistas, pra quê? militância sindical e o drama da identidade profissional - Silva, Marco Antonio Roxo da (2008)
The main aim of this thesis is to investigate the Brazilian journalists process of becoming professionals in the 80s. During this period, the journalists negotiated among themselves and with other agents, in a conflicted and dramatic way, the outlines of their identities as professionals. We decided to adopt this chronological reference due to the fact that the body of journalists had during this period an intense participation in the journalistic field centered in two ways of acting: some worked as an intense of forum for journalists debates in relation to their identities, and others had a fundamental role in defining the professional frontiers of these agents, behaving in an incisive way to form journalists as a body and as a class. This pattern of behavior enabled us to map the discursives matrixes which journalists used to define, in a tense and ambiguous way, their role in society. In order to organize methodically this field s force, we structured the debate focusing on three ideal kinds of journalists: the intellectual, the worker and the professional who are of the studied period, related to the reformers of the past, the companies and the union, respectively. We will identify the meaning of the journalist s job after the 80s using this typographical conflict